Examining the effects of cigarette smoke on mouse lens through a multi OMIC approach - Shahid Y. Khan (Nature Portfolio, 2021)
Abstract Here, we report a multi OMIC (transcriptome, proteome, and metabolome) approach to investigate molecular changes in lens fiber cells (FC) of mice exposed to cigarette smoke (CS). Pregnant mice were placed in a whole-body smoke chamber and a few days later pups were born, which were exposed to CS for 5 hours/day, 5 days/week for a total of 3½ months. We examined the mice exposed to CS for CS-related cataractogenesis after completion of the CS exposure but no cataracts were observed. Lenses of CS-exposed and age-matched, untreated control mice were extracted and lens FC were subjected to multi OMIC profiling. We identified 348 genes, 130 proteins, and 14 metabolites exhibiting significant (p < 0.05) differential levels in lens FC of mice exposed to CS, corresponding to 3.6%, 4.3%, and 5.0% of the total genes, protein, and metabolites, respectively identified in this study. Our multi OMIC approach confirmed that only a small fraction of the transcriptome, the proteome, and the metabolome was perturbed in the lens FC of mice exposed to CS, which suggests that exposure of CS had a minimal effect on the mouse lens. It is worth noting that while our results confirm that CS exposure does not have a substantial impact on the molecular landscape of the mouse lens FC, we cannot rule out that CS exposure for longer durations and/or in combination with other morbidities or environmental factors would have a more robust effect and/or result in cataractogenesis.